TWO-DIMENSIONAL CODE READING DEVICE, METHOD FOR READING TWO-DIMENSIONAL CODE, METHOD FOR MANAGING MANUFACTURE HISTORY INFORMATION ABOUT MEMBER WITH SUBSTANTIALLY CIRCULAR SHAPE OF SECTION PERPENDICULAR TO CENTER AXIS, AND METHOD FOR MANUFACTURING THE MEMBER BY USING THE MANAGING METHOD - SAKIYAMA MASAMI; TANIDA MUTSUMI; YOSHIDA MASAYUKI (2015)
[Problem to be Solved] Provided are a two-dimensional code reading device and a two-dimensional code reading method for reading a two-dimensional code carved in a member having a substantially circular section orthogonal to the central axis thereof, as well as a method of controlling manufacturing history information using the reading device and a method of manufacturing the member using the control method. [Solution] A concave portion 11 carved in the member on which a two-dimensional code 10 is formed has a pair of a first inclined portion 12 and a second inclined portion 13 which are inclined so as to form an angle ² with respect to a normal-line direction R of a surface of the member. A two-dimensional code reading device 20 is provided with image pickup means 22 which receives light reflected from either of the first inclined portion 12 and the second inclined portion 13 in a direction forming an angle ¸ satisfying expression (1) with respect to the normal-line direction R, and illumination means 21 which irradiates either of the inclined portions from a direction forming an angle ± satisfying expression (2) with respect to the normal-line direction R: 30 ¢ ° ¤ ¸ ¤ 35 ¢ ° ¸ = ¸ - 180 ¢ ° + ± + 2 ¢ ² where ² is less than 90°, ¸ is not less than -10° but not more than 10°, and ¸ and ± are angles in a turn direction reverse to a turn direction at which either of the inclined portions forms the angle ² with respect to the normal-line direction R.